Empowering Rural Entrepreneurship: Innovating Through Village-Owned Enterprises - Puji Hadiyanti; Daddy Darmawan; Karta Sasmita; Muhammad Mawardi Jafar; Henny Herawaty Br Dalimunthe (Universitas Negeri Semarang, 2024)
The lack of formal job access and limited employment sectors in rural areas have increased unemployment and poverty rates. Expanding rural entrepreneurship is a potential solution to create job opportunities and increase rural communities' income. Therefore, a comprehensive strategy needs to be developed to strengthen social capital and support the sustainability of Village-Owned Enterprises (BUMDes). This research examines efforts to build entrepreneurship in the village environment through innovations implemented in BUMDes. It explores innovative strategies used by BUMDes to enhance the village's economic potential, focusing on developing local businesses, empowering the community, and improving access to resources. The research methods used include surveys, interviews, and quantitative data analysis. The results show that BUMDes and their partners have a good relationship, and BUMDes managers regularly communicate with their partners. However, BUMDes managers must also establish good communication with community members and local leaders. If BUMDes managers can build strong relationships with village residents, they will find it easier to obtain support, information, and helpful advice for managing BUMDes. BUMDes managers are categorized as having a high level of support for those in the community who have difficulty accessing business capital loans. Furthermore, the results of the path analysis reveal that there is no statistically significant relationship between the variables of experience (X1), motivation (X1), ICT media role (X3), and social capital capacity (Y1). This means that in the context of this study, these three independent variables do not significantly impact social capital capacity (Y1). These findings can guide the government, community, and relevant stakeholders in supporting efforts to build rural entrepreneurship through BUMDes innovations.